2022
DOI: 10.1039/d2cp02911a
|View full text |Cite
|
Sign up to set email alerts
|

The reduction reaction of carbon dioxide on a precise number of Fe atoms anchored on two-dimensional biphenylene

Abstract: In a recent accomplishment, a new two-dimensional allotrope of carbon-biphenylene (BP) was experimentally synthesized [Fan et al., Science, 372, 852-856 (2021)]. The BP sheet is composed of four-, six-, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…43 Then, extensive studies have been carried out to reveal the unique physical and chemical properties of this novel graphene-like carbon material. [44][45][46][47][48] With regular distributed four-, six-, eightmembered ''holes'' and very active atoms and chemical bonds, 2D BPN sheets are expected to exhibit an improved performance as a potential anchoring material. However, although several studies have demonstrated that the pure BPN monolayer possesses superior HER, 44 OER, 46 CO 2 RR, 47 and methane oxidation reaction activities, 48 a systematic analysis of the NRR mechanisms upon the decoration of this novel 2D material with small transition metal clusters is still worthy to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…43 Then, extensive studies have been carried out to reveal the unique physical and chemical properties of this novel graphene-like carbon material. [44][45][46][47][48] With regular distributed four-, six-, eightmembered ''holes'' and very active atoms and chemical bonds, 2D BPN sheets are expected to exhibit an improved performance as a potential anchoring material. However, although several studies have demonstrated that the pure BPN monolayer possesses superior HER, 44 OER, 46 CO 2 RR, 47 and methane oxidation reaction activities, 48 a systematic analysis of the NRR mechanisms upon the decoration of this novel 2D material with small transition metal clusters is still worthy to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The C atoms on the 4‐membered ring of biphenylene can facilitate the activation of O 2 ; hence, biphenylene exhibits an excellent oxygen reduction reaction (ORR) performance [25] . Furthermore, introducing heteroatoms can influence biphenylene‘s electronic, magnetic, and catalytic properties, which leads to the enhanced catalytic activity of heteroatom‐doped biphenylene for ORR, hydrogen evolution reaction, and CO 2 reduction [26–29] . This situation inspired us to explore the catalytic performance of biphenylene and its doped structures as cathode catalysts for LOBs.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Furthermore, introducing heteroatoms can influence biphenylene's electronic, magnetic, and catalytic properties, which leads to the enhanced catalytic activity of heteroatom-doped biphenylene for ORR, hydrogen evolution reaction, and CO 2 reduction. [26][27][28][29] This situation inspired us to explore the catalytic performance of biphenylene and its doped structures as cathode catalysts for LOBs.…”
Section: Introductionmentioning
confidence: 99%
“…Biphenylene also demonstrates excellent catalytic properties due to its good metallic properties. For instance, it can be used in hydrogen evolution reaction with atomic doping, [14,15] CO2 reduction reaction with Fe atoms doping, [16] and electrochemical nitrogen reduction reaction with Mo atoms doping. [17] Furthermore, it can be applied in superlattice nanostructures to achieve lower thermal conductivity for nanodevices.…”
mentioning
confidence: 99%